1998
DOI: 10.1016/s0550-3213(98)00486-6
|View full text |Cite
|
Sign up to set email alerts
|

Monopoles and hadron spectrum in quenched QCD

Abstract: We report the preliminary results of the studies of hadron spectrum under the background of abelian and monopole gauge elds in quenched Wilson SU(3) QCD. Abelian gauge elds alone reproduce the same chiral limit as in the full case. Critical hopping parameter c and m are the same in both cases. We need more time to get a denite result in the case of monopole background. The photon contribution do not produce any mass gap in the chiral limit ( = c 0:17). The behavior is similar to those in the free photon case f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In previous studies of lattice QCD, instantons have been found in QCD vacuums [40], and the relations between the instantons and Abelian monopoles have been studied [41]. The hadron masses were calculated from the background fields of Abelian monopoles [42]. The fermion zero modes have been derived from the background fields of magnetic monopoles [43,44].…”
Section: Jhep09(2020)113mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of lattice QCD, instantons have been found in QCD vacuums [40], and the relations between the instantons and Abelian monopoles have been studied [41]. The hadron masses were calculated from the background fields of Abelian monopoles [42]. The fermion zero modes have been derived from the background fields of magnetic monopoles [43,44].…”
Section: Jhep09(2020)113mentioning
confidence: 99%
“…The monopole current k i µ in SU(3) [4,42,69] is defined on the dual site * n such that it satisfies the condition i k i µ ( * n) = 0 as follows:…”
Section: The Monopole Density and The Length Of The Monopole Loopsmentioning
confidence: 99%
“…It is interesting to study the influence of Abelian dominance on chiral symmetry breaking and the hadron spectrum; in [26] it has been found that SU(2) Abelian projected fields give a chiral condensate which closely resembles the results of strongly coupled gauge theory. In [27] quenched hadron spectra in Abelian gauge fields, ex-tracted by maximal Abelian projection have been studied: the ratios of the hadron mass to the square root of the string tension of the Abelian fields are similar to those of the full SU(3) theory. The authors concluded that they have found Abelian dominance (and monopole dominance) for the hadron spectra.…”
Section: Introductionmentioning
confidence: 99%
“…are closely related to the Abelian monopoles defined in the maximally Abelian gauge (MAG) [1,2]. A number of arguments supports the statement that the Abelian monopoles found in the MAG are important physical fluctuations surviving the cutoff removal: scaling of the monopole density at T = 0 according to dimension 3 for infrared (percolating) cluster [3]; Abelian and monopole dominance for a number of infrared physics observables (string tension [3,4,5], chiral condensate [6], hadron spectrum [7]). It has been recently argued that the MAG is a proper Abelian gauge to find gauge invariant monopoles since t'Hooft-Polyakov monopoles can be identified in this gauge by the Abelian flux, but this is not possible in other Abelian gauges [8].…”
Section: Introductionmentioning
confidence: 87%